The Effect of Rooting and Acclimatization Media on the Success of Acclimatization of Tembesu (Fagraea fragrans (Roxb.) Miq.) - Ganis Citra Purmadewi; Arum Sekar Wulandari; Ratna Uli Damayanti Sianturi (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2019)
Acclimatization is an attempt to conditioning the plantlets or micro shoots propagated by tissue culture to the environment outside the bottle. This study aims to know the effect of rooting and media acclimatization on the growth of tembesu plantlets in vitro cultures. Two experiments were conducted, these were (1) rooting (in vitro and ex vitro), and (2) type of acclimatization media ( 100% sand, cocopeat + rice husk, sand + cocopeat , sand, rice husk, and sand + cocopeat + rice husk). Based on the data analysis rooting significantly affects the variables growth (percentage of survival and the number of roots) at the acclimatization stage of tembesu.The percentage of planlets survival in the acclimatization are 80percent for in vitro rooting and 75percent for ex vitro rooting, while on stage after acclimatization percentage of survival are 75 percent for in vitro rooting and 67 percent for ex vitrorooting. In vitro rooting have a better growth than ex vitro rooting, but the plants grown from ex vitro rooting are more resistant to stress. The best acclimatization media for tembesu is 100 percent of sands.